Rare Primary Adenocarcinoma of the Broad Ligament: Report of Two Cases and a Literature Review. (August 2016) - Miyoshi, Ai; Miyatake, Takashi; Hara, Takeya; Komiya, Shinnosuke; Komura, Naoko; Tanaka, Asuka; Kanao, Serika; Takeda, Masumi; Mimura, Mayuko; Nagamatsu, Masaaki; Yamasaki, Masaru; Yokoi, Takeshi
Malignant primary tumors arising in the uterine broad ligament are extremely rare, and only 26 cases have been reported to date. We describe 2 new cases of primary adenocarcinoma of the broad ligament, and we review the previous literature on such rare tumors. In Case 1, a 71-year-old woman presented with a 2-month history of increased yellow vaginal discharge and lower abdominal pain during bowel movement. Transvaginal sonography revealed a 6.5 cm mass located on the dorsum of the uterus and a 7.0 cm mass (with cystic and solid parts) near the right adnexa. We postoperatively diagnosed the mass as a high-grade serous carcinoma of the broad ligament (pT3cNXM0). The patient is currently receiving adjuvant chemotherapy with paclitaxel and carboplatin. In Case 2, during a complete medical checkup a 43-year-old woman was found to have a pelvic mass indicative of leiomyoma. Transvaginal sonography revealed a 3.8 cm mass located on the dorsum of the uterus. Following surgery, we diagnosed the mass as a clear cell adenocarcinoma of the broad ligament (pT2bN1M0). This patient is also now receiving adjuvant chemotherapy with paclitaxel and carboplatin.